2018
DOI: 10.1016/j.solener.2018.08.033
|View full text |Cite
|
Sign up to set email alerts
|

How measurement protocols influence the dynamic J-V characteristics of perovskite solar cells: Theory and experiment

Abstract: The dynamic effects observed in the J-V measurements represent one important hallmark in the behavior of the perovskite solar cells. Proper measurement protocols (MPs) should be employed for the experimental data reproducibility, in particular for a reliable evaluation of the power conversion efficiency (PCE), as well as for a meaningful characterization of the type and magnitude of the hysteresis. We discuss here several MPs by comparing the experimental J-V characteristics with simulated ones using the dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 43 publications
1
50
0
Order By: Relevance
“…It has been reported that one of the relevant origins of the inverted hysteresis is the ion migration in PSCs 9,27,28 . The migration of different ionic species in perovskite films could cause the J-V hysteresis, the degree of which depends on the voltage scan rates 9 , directions (forward-to-reverse or reverse-to-forward bias scans) 29 , ranges 27,30 , and temperature 31 . Thus, we measured J-V curves in the consecutive reverse-to-forward scans (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that one of the relevant origins of the inverted hysteresis is the ion migration in PSCs 9,27,28 . The migration of different ionic species in perovskite films could cause the J-V hysteresis, the degree of which depends on the voltage scan rates 9 , directions (forward-to-reverse or reverse-to-forward bias scans) 29 , ranges 27,30 , and temperature 31 . Thus, we measured J-V curves in the consecutive reverse-to-forward scans (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[52] which considers the integrated power output of the solar cells in fwd (SC to OC) and bwd (OC to SC) scan directions. Based on Nemnes et al [53][54][55] this method is useful for the determination of the HI for normal and inverted hysteresis in non-crossing JV curves. If the HI approaches 0, the solar cell would have negligible hysteresis.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Nemnes et al [33] investigated the influences of measurement techniques on the dynamic J-V performance, indicating that the extent and type of the J-V hysteresis were dramatically dependent on the pre-poling conditions and the bias scan rate. The "S" shaped J-V curves shown in Figure 7 were consistent with the findings in reference [33], if the perovskite solar cell was pre-poled at open-circuit, the forward scan curve present a crossover point with the following reverse scan curve. The overall PCE performances present here had no advantages compared to the excellent published work [34] due to the poor surface morphology and crystal quality of the perovskite films, on which our future work would focus.…”
Section: Energies 2019 12 X For Peer Review 6 Of 12mentioning
confidence: 99%